Peppa's Pumpkin Party (Penguin Random House, 2019)
It is Halloween and Peppa's family are having a Pumpkin Party! Everyone comes to play in their spookiest costumes, even Madame Gazelle! With a bright green neon cover, this storybook is perfect for reading at Halloween with little Peppa Pig fans.
Keywords: English story book